Caminhos e descaminhos do ouro das minas de Castelo, entre as capitanias do Espírito Santo e da Paraíba do Sul (1640-1771) - Ribeiro, Rafaela Machado (2023)
In this work, we seek to understand how the explorations in the so-called Castelo mines at the beginning of the 18th century, carried out by men like Pedro Bueno Cacunda from São Paulo, reveal the economic, territorial and political relations between different parts of Portuguese America, in particular, the captaincies of Paraíba do Sul and Espírito Santo. For this, we consider analyzing the governmental and social dynamics of these two captaincies in the immediate general context, but also in the one that preceded the beginning of the local mining stage, in order to demonstrate that since the 16th century, still at the beginning of the captaincy system, Espírito Santo Santo and Paraíba do Sul were linked by territorial, political and economic ties. Using different sources, some of them unpublished, this work endeavored to demonstrate the formation of dynamic local networks, more or less autonomous, with private interests that, far from excluding or jettisoning metropolitan power, were part of the very logic of existence of the Portuguese government. The exploration of the Castelo mines and the frequent presence of Paulistas within the territory of these captaincies, still so relegated by historiography, demonstrate the complex tangle of interests present within the colony, as well as the forms of balance sought by Portugal in the administration of subjects so necessary, but also so distant.